STRATEGI GURU PAI DALAM MENERAPKAN ETIKA KOMUNIKASI PADA SISWA SMP MIFTAHULULUM BULULAWANG - Wahyu Dwi Lestari (Jurnal Cakrawala Ilmiah, 2026)
Communication ethics is an important part of students’ character development, particularly amid changes in communication patterns influenced by social environments and digital media. Islamic Religious Education (PAI) teachers have a strategic role in guiding students to communicate politely and in accordance with Islamic values. This study aims to examine the strategies used by PAI teachers in implementing communication ethics among students at Miftahululum Bululawang Junior High School and to identify supporting and inhibiting factors. This study employed a descriptive qualitative approach using field research. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model and validated through triangulation. The findings indicate that exemplary behavior and school culture are the most prominent strategies. Teachers provide examples of polite communication by using krama inggil Javanese or polite Indonesian with a gentle tone. Habituation, discussion forums, and guidance also help students reduce harsh language, develop self-control, and respect others. The findings indicate that communication ethics is more effectively developed when consistent examples are reinforced by a supportive school environment.